Trans-Fat Labeling in Packaged Foods Sold in Brazil Before and After Changes in Regulatory Criteria for Trans-Fat-Free Claims on Food Labels - Barros, Beatriz Vasconcellos de; Proença, Rossana Pacheco da Costa; Kliemann, Nathalie; Hilleshein, Daniele; Souza, Amanda Alves de; Cembranel, Francieli; Bernardo, Greyce Luci; Uggioni, Paula Lazzarin; Fernandes, Ana Carolina (Frontiers in Nutrition, 2022)
Consumption of industrially produced trans-fat acids (TFA) is a public health concern. Therefore, it is important that information on TFA in packaged foods be clearly informed to consumers. This study aimed to assess the evolution of TFA information presented in packaged foods sold in Brazil in 2010 and 2013, before and after the introduction of stricter regulatory requirements for TFA-free claims on food labels. A repeated cross-sectional study was performed through food label censuses of all packaged foods available for sale in two stores from the same supermarket chain, totaling 2,327 foods products in 2010 and 3,176 in 2013. TFA-free claims and information indicating TFA in the ingredients list and nutrition facts label were analyzed by descriptive statistics and Pearson’s chi-square test. There was a 14% decrease in the use of ingredients containing or potentially containing industrially produced TFA (i-TFA), according to analysis of the ingredients list. However, when analyzing foods by groups, it was found that this decrease was significant only for group A (bakery goods, bread, cereals, and related products; from 59 to 35%, p < 0.001). By contrast, food group F (gravies, sauces, ready-made seasonings, broths, soups, and ready-to-eat dishes) showed a 5% increase in i-TFA. The use of specific terms for i-TFA decreased between 2010 and 2013, but there was an increase in the use of alternative terms, such as vegetable fat and margarine, which do not allow consumers to reliably identify whether a food product is a possible source of i-TFA. There was an 18% decrease in the use of TFA-free claims in products containing or potentially containing i-TFA. However, almost one-third of foods sold in 2013 were false negatives, that is, foods reported to contain 0 g of TFA in the nutrition facts label or with TFA-free claims but displaying specific or alternative terms for i-TFA in the ingredients list. The results indicate that adoption of stricter requirements for TFA-free claims on food labels in Brazil helped reduce the prevalence of such claims but was not sufficient to decrease i-TFA in industrialized foods sold in supermarkets.